Development and characterization of hydrogels based on natural polysaccharides : policaju and chitosan - Soares, Paulo A. G. (2014)
The development of hydrogels based on natural polysaccharides was investigated by preparing mixtures of policaju/chitosan at weight ratios of 1:4 and 2:3. Utilizing dynamic light scattering (DLS) techniques for these mixtures, an increase on the hydrodynamic particle radius was observed varying their pH from 3.0 to 12.0. Furthermore, a reduction of ζ-potential was also observed for the same pH interval. Following rounds of drying/hydration cycles at a specific pH value, hydrogel matrices were formed. The pore size distribution of these formed hydrogels was examined using scanning electron microscopy. Further FT-IR analyses confirmed a physical interaction between the polysaccharides policaju and chitosan. Swelling experiments revealed water uptake values, after 24h of immersion in water, close to 270% for 1:4, and 320% for 2:3 hydrogels. Finally, rheological measurements were then conducted in order to confirm hydrogel viscoelastic features. These results indicate a promising road to biomaterials fabrication and biomedical applications. Copyright © 2014 Elsevier B.V. All rights reserved.